Ion lens imaging method and system for ion molecular reaction - LUAN ZHIWEN; WANG XING'AN; QIU QIMING (2020)
The invention relates to an ion lens imaging method and system for ion molecular reaction, and belongs to the field of cross beam reaction/ion imagers. According to the method and system, ions are notinterfered by an electric field when entering a reaction area through an ion molecule reaction area arranged by a pulse electrode, the irons enter an ion focusing area through the pulse electrode after ion molecule reaction, and the ions at the same speed are focused, and then pass through a flight amplification area composed of simple electrodes and hit a phosphorescent screen to be detected. The method can be used for detecting microcosmic reaction details such as a reaction cross section and a product scattering angle of ion-related reaction. 本发明涉及一种用于离子分子反应的离子透镜成像方法及系统，属于交叉束反应/离子成像仪领域。包括：通过脉冲电极设置的离子分子反应区，使离子在进入反应区时不受电场干扰，离子分子反应后通过脉冲电极进入离子聚焦区，将具有相同速度的离子进行聚焦，聚焦后经由简状电极组成的飞行放大区后打到磷光屏上进行探测。本发明可用于离子相关反应的反应截面、产物散射角等微观反应细节的探测。